2017
DOI: 10.1109/tbcas.2017.2699189
|View full text |Cite
|
Sign up to set email alerts
|

A Multimodal Framework Based on Integration of Cortical and Muscular Activities for Decoding Human Intentions About Lower Limb Motions

Abstract: In this study, a multimodal fusion framework based on three different modal biosignals is developed to recognize human intentions related to lower limb multi-joint motions which commonly appear in daily life. Electroencephalogram (EEG), electromyogram (EMG) and mechanomyogram (MMG) signals were simultaneously recorded from twelve subjects while performing nine lower limb multi-joint motions. These multimodal data are used as the inputs of the fusion framework for identification of different motion intentions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…By recognizing the patients' active motor abilities or movement intentions, the human-in-the-loop rehabilitation robotic systems are able to optimize participation and support the patients only as little as needed. 3 However, stroke patients' active involvements in the existing rehabilitation robotic systems are mostly considered from biomechanical and bioelectrical viewpoints, where the patients' active force/position signals 4,5 or electrical activities of the brain and the muscles 6,7 were recorded.…”
Section: Introductionmentioning
confidence: 99%
“…By recognizing the patients' active motor abilities or movement intentions, the human-in-the-loop rehabilitation robotic systems are able to optimize participation and support the patients only as little as needed. 3 However, stroke patients' active involvements in the existing rehabilitation robotic systems are mostly considered from biomechanical and bioelectrical viewpoints, where the patients' active force/position signals 4,5 or electrical activities of the brain and the muscles 6,7 were recorded.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers used statistical methods and machine learning approaches to evaluate the variations in gait and classify the gait features of post-stroke patients and healthy adults. C. Cui et al demonstrated multi-modal physiological features (EMG, motion, and ground reaction force) and machine learning algorithms to discriminate between post-stroke and healthy gait [ 32 , 60 ]. Park et al demonstrated the prediction of stroke-impaired gait using the ground reaction force and acceleration data through a machine learning approach [ 5 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contingent visual and proprioceptive feedback about the user's EEG and EMG activity is provided in the form of velocity modulation during functional task training. Participants started the real-time operation task with their paretic arm and hand relaxed in a comfortable rest position to reach one of the three targets around the workspace ( Fig.21(a)-(b)), while supinating the wrist and opening their hands [181,182]. It helped the patients accomplish complicated target task with the EEG-EMG biofeedback system and enhance the motion ability of patients.…”
Section: Eeg-emg Biofeedback To Human Bodiesmentioning
confidence: 99%